Gamma exposure from building materials – A dose model with expanded gamma lines from naturally occurring radionuclides applicable in non-standard rooms. (20th January 2018) - Croymans, Tom; Leonardi, Federica; Trevisi, Rosabianca; Nuccetelli, Cristina; Schreurs, Sonja; Schroeyers, Wouter
Highlights: The number of considered gamma emission lines influences the absorbed dose rate in air (DA ). A novel model including 1845 gamma emission lines (EGDA) was developed. The sensitivity of the EGDA model for different parameters was evaluated. Density and thickness are the most important parameters influencing the DA . The EGDA allows performing more accurate dose assessments as alternative for the ACI. Abstract: Building materials are a significant source of gamma rays exposure due to the presence of naturally occurring radionuclides. In order to protect the public from harmful radiation, the European Basic Safety Standards (Council directive 2013/59/Euratom) (European Council, 2014) introduced a one-size-fits-all building(s) (materials) activity concentration index (ACI) based on a limited set of gamma lines. The ACI is considered " as a conservative screening tool for identifying materials that may cause the reference level (i.e. 1 mSv/y) laid down in article 75(1) to be exceeded " . Regarding calculation of dose, many factors such as density and thickness of the building material, as well as factors relating to the type of building, and the gamma emission data need to be taking into account to ensure accurate radiation protection. In this study the implementation of an expanded set of 1845 gamma lines, related to the decay series of 238 U, 235 U and 232 Th as well as to 40 K, into the calculation method of Markkanen (1995), is discussed. The expanded calculation method is called the Expanded Gamma Dose Assessment (EGDA) model. The total gamma emission intensity increased from 2.12 to 2.41 and from 2.41 to 3.04 for respectively the 238 U and 232 Th decay series. In case of 40 K a decrease from 0.107 to 0.106 is observed. The 235 U decay series is added, having a gamma emission intensity of 3.1. In a standard concrete room, the absorbed dose rates in air (DA ) per unit of activity concentration of 0.849, 0.256, 1.08, 0.0767 nGy/h per Bq/kg are observed. The use of weighted average gamma lines increased the DA with 6.5% and 1% for respectively the 238 U and 232 Th decay series. A decrease of 4.5% is observed in the DA of 235 U decay series when using the weighted average gamma lines in comparison to its non-averaged variant. The sensitivity of the EGDA model for density, wall thickness, presence of windows and doors and room size is investigated. Finally, a comparison of the index and dose calculations relevant for the dose assessment within the European legislative framework applicable towards building materials is performed. In cases where the ACI and density and thickness corrected dose calculation of Nuccetelli et al. (2015) cannot provide guidance, the EGDA allows performing more accurate dose assessment calculations leading to effective doses which can be several 100 µSv/y lower.